The major factor of left ventricular systolic dysfunction in patients with cardiac amyloidosis: Amyloid overload or microcirculation impairment? - Lu, Jianyao; Zhao, Peijun; Qiao, Jinhan; Yang, Zhaoxia; Tang, Dazhong; Zhou, Xiaoyue; Huang, Lu; Xia, Liming (Frontiers in Cardiovascular Medicine, 2023)
Purpose: Amyloid overload and microcirculation impairment are both detrimental to left ventricular (LV) systolic function, while it is not clear which factor dominates LV functional remodeling in patients with cardiac amyloidosis (CA). The purpose of this study was to investigate the major factor of LV systolic dysfunction using cardiac magnetic resonance imaging. Materials and Methods: Forty CA patients and 20 healthy controls were included in this study. The CA group was divided into two subgroups by the left ventricular ejection fraction (LVEF): patients with reduced LVEF (LVEF<50%, rLVEF), and patients with preserved LVEF (LVEF≥50%, pLVEF). The scanning sequences included cine, native and post-contrast T1 mapping, rest first-pass perfusion and late gadolinium enhancement. Perfusion and mapping parameters were compared among the three groups. Correlation analysis was performed to evaluate the relationship between LVEF and mapping parameters, as well as the relationship between LVEF and perfusion parameters. Results: Remarkably higher native T1 value was observed in the rLVEF patients than the pLVEF patients (1442.2±85.8ms vs. 1407.0±93.9ms, adjusted P=0.001). The pLVEF patients showed significantly lower slope dividing baseline signal intensity (slope%BL) (rLVEF vs. pLVEF, 55.1±31.0 vs. 46.2±22.3, adjusted P=0.001) and a lower maximal signal intensity subtracting baseline signal intensity (MaxSI-BL) (rLVEF vs. pLVEF, 43.5±23.9 vs. 37.0±18.6, adjusted P=0.003) compared to the rLVEF patients. CA patients required more time to reach the maximal signal intensity than the controls did (all adjusted P<0.01). There was no significant correlation between LVEF and first-pass perfusion parameters, while significant negative correlation was observed between LVEF and native T1 (r=-0.434, P=0.005) in CA patients. Conclusion: Amyloid overload in the myocardial interstitium may be the major factor of LV systolic dysfunction in CA patients, other than microcirculation impairment.